2006
DOI: 10.1007/s00420-006-0136-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of perfluorinated substances in an adult German population in southern Bavaria

Abstract: Our data agree well with results of other recent studies in Europe and suggest that the current exposure of the adult German population is lower than the exposure of the US and Canadian population. The sources of human exposure are currently not well understood. Toxicological implications are restricted to animal studies and occupational investigations not adequate for quantitative risk assessment in humans. Overall, more scientific research is necessary to characterize the body burden of PFCs (especially for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
66
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 28 publications
17
66
2
2
Order By: Relevance
“…With regard to gender, levels of PFOS but not PFOA in blood were significantly higher in men than in women. This result for PFOS was in line with those of other studies 17,18,20,23,26) . One reason for this sex difference may be the effects of pregnancy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With regard to gender, levels of PFOS but not PFOA in blood were significantly higher in men than in women. This result for PFOS was in line with those of other studies 17,18,20,23,26) . One reason for this sex difference may be the effects of pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…Most previous studies used serum or plasma as a biological medium to evaluate the body burden of PFOS and PFOA, and mean ratios of serum to whole blood concentrations were reported to be approximately 2.3 for PFOS and 2.0 for PFOA 16) . The estimated median serum level of PFOS in our study (13.3 ng ml −1 ), using the ratio of 2.3, was similar to those in serum or plasma reported for Germany 17) , Australia and Japan (10.9−18.3 ng ml −1 ) 18,19) , higher than those reported for Italy 20) Korea and Vietnam (5.6−8.4 ng ml −1 ) 21,22) and lower than those in the U.S. 23,24) and Denmark (30.2−35.8 ng ml −1 ) 25) . On the other hand, the estimated median serum level of PFOA (4.2 ng ml ) was similar to those reported for Germany 17) , Denmark 25) , the U.S. 23,24) , Italy 20) , Australia and Japan (3.6−6.8 ng ml −1 ) 18,19) and higher than those in Vietnam and Korea (0.58−1.6 ng ml −1 ) 21,22) .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…PFOA, instead of PFOS, was the dominant analyte (Pan et al, 2010;Guo et al, 2011). Consistent with other studies, the univariate analysis showed that concentrations of PFOA, PFNA and PFOS were significantly correlated with age, and concentrations of PFOA, PFNA, PFDA and PFOS appeared to be higher in males than those in females (Calafat et al, 2007;Fromme et al, 2007;Holzer et al, 2008;Haug et al, 2009;Zhang et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…6. PFOS, PFOA and PFHxS concentrations in human blood (*, serum data, or whole blood data converted to serum basis by multiplying by a factor of 2) of the general population (male adults; except for Sweden: female adults) in several cities all over the world (2000-05); data adapted from references that are cited following the data: China [41] ; USA, Poland, South Korea, Belgium, Malaysia, Brazil, Japan (2002), Colombia, Italy, India [26] ; Canada [160] ; Japan (2003) [138] ; Australia [161] ; Norway [39] ; Sweden [51] ; Germany [162] ; Sri Lanka. [163] Chinese cities no age-related differences were observed.…”
Section: Levels and Trends In Humansmentioning
confidence: 99%